MUSIC AND AROMATHERAPY: A GOOD COMBINATION FOR REDUCING ANXIETY AND STABILIZING NON-INVASIVE HEMODYNAMIC STATUS IN PATIENTS IN THE INTENSIVE CARE UNIT - Ferry Kumala; Diyah Fatmasari; Kurniati Puji Lestari; Suharyo Hadisaputro (Belitung Nursing Journal, 2018)
Background: Combining musical and aromatherapy therapy is expected to have a stronger effect in the reduction of anxiety and non-invasive hemodynamic stability. Objective: To examine the effect of the combination of music and aromatherapy on anxiety and non-invasive hemodynamic in patients in the intensive care unit. Methods: This was a quasi-experimental study with non-equivalent group. An experimental group was given a combined musical and aromatherapy, while a control group was given music therapy. Thirty respondents were selected using accidental sampling, with 15 randomly assigned in the music group and the combination group. HARS scale (Hamilton Anxiety Rating Scale) was used to measure anxiety. Non-invasive hemodynamic status such as blood pressure and heart rate were documented in the observation sheet. Paired t-test and one-way ANOVA were used for data analysis. Results: There were significant effects of combination therapy on anxiety (p=0.001), diastole (p=0.004) and heart rate (p=0.031), but no significant effect on systole (p=0.387). The music therapy alone had a significant effect on anxiety (p=0.001), systole (p=0.047), and diastole (p=0.037). Conclusion: The combination of music and aromatherapy had a greater effect than the music therapy alone in decreasing anxiety and stabilizing diastolic blood pressure and heart rate. This therapy can be used as an alternative in nursing interventions and as an input to develop standard of operational procedure for anxiety and non-invasive hemodynamic stability.